2021
DOI: 10.1007/s00415-021-10458-0
|View full text |Cite
|
Sign up to set email alerts
|

Myoclonus and cerebellar ataxia associated with COVID-19: a case report and systematic review

Abstract: Background Since the beginning of the coronavirus disease 2019 (COVID-19) pandemic in December 2019, neurological manifestations have been recognized as potential complications. Relatively rare movement disorders associated with COVID-19 are increasingly reported in case reports or case series. Here, we present a case and systematic review of myoclonus and cerebellar ataxia associated with COVID-19. Methods A systematic review was performed according to the Preferred Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 67 publications
4
61
2
2
Order By: Relevance
“…Encephalopathies, which are apparently linked to COVID-19 infection, seem to share a coordination and gait impairment, denoting a cerebellar syndrome. Poor coordination and ataxia have been extensively described as rare and treatable post-infectious or para-infectious, immune-mediated phenomena associated with COVID-19 [2]. In some cases, opsoclonus and myoclonus have also been described in association with ataxia, denoting a specific condition named opsoclonus-myoclonus-ataxia syndrome (OMAS): this is a rare disorder that is thought to be immune-mediated, with primarily paraneoplastic or para-infectious etiologies [2].…”
Section: Dear Editormentioning
confidence: 99%
“…Encephalopathies, which are apparently linked to COVID-19 infection, seem to share a coordination and gait impairment, denoting a cerebellar syndrome. Poor coordination and ataxia have been extensively described as rare and treatable post-infectious or para-infectious, immune-mediated phenomena associated with COVID-19 [2]. In some cases, opsoclonus and myoclonus have also been described in association with ataxia, denoting a specific condition named opsoclonus-myoclonus-ataxia syndrome (OMAS): this is a rare disorder that is thought to be immune-mediated, with primarily paraneoplastic or para-infectious etiologies [2].…”
Section: Dear Editormentioning
confidence: 99%
“… 4 Recently, Chan et al reported a case and systematically reviewed the clinical features of 51 cases of myoclonus presenting within 1 month of COVID-19 symptoms with associated ataxia in 40% of patients and cognitive changes in 30% of patients. 5 The likely pathophysiology behind the myoclonus was presumed to be parainfectious or neuro-inflammatory and most cases improved with immunotherapy or spontaneously within 2 months of onset. 4 , 5 The onset of movement disorder in our patient was 2 months after initial COVID-19 symptoms without any improvement or worsening with time.…”
Section: Discussionmentioning
confidence: 99%
“… 1 COVID-19-related movement disorders include myoclonus, opsoclonus, and ataxia and are presumed to be parainfectious or post-infectious in etiology. 4 , 5 Functional movement disorders (FMDs) are also being reported after COVID-19 infection as well after COVID-19 vaccination. 6 We want to report a case of a 54-year-old man who presented to post-COVID clinic at the University of Iowa with abnormal repetitive movement of the head, which started 2 months after SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst these disorders of coagulation and endothelial integrity represent potential drivers of large vessel cerebrovascular disease, they also raise the possibility that impairment of the microvasculature might be involved in some of the less clear-cut neurological presentations, such as prolonged disorders of consciousness (including akinetic-mutism states) [63,[100][101][102], myoclonus (a relatively common complication with over 50 cases reported in the literature, which is seemingly unrelated to hypoxic ischaemic brain injury [103]), or even on the long-term cognitive outcomes of those who recover. Indeed, neuroimaging studies have commonly described cerebral microhaemorrhages occurring in those with severe COVID-19, reminiscent of microangiopathic disorders such as amyloid and hypertensive angiopathies [100,104,105], a phenomenon borne out in pathology series [32,75,100,106].…”
Section: Neurovascular and Thromboembolic Diseasementioning
confidence: 99%